2010
DOI: 10.1093/europace/euq297
|View full text |Cite
|
Sign up to set email alerts
|

Transseptal puncture using minimally invasive echocardiography during atrial fibrillation ablation

Abstract: Intracardiac echocardiography-TEE is safe and well tolerated for the guidance of transseptal catheterization during AF ablation. Moreover, this technique was performed without requiring any anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Although general anesthesia is not necessary for this technique, additional femoral vein puncture is an important limitation like the cost of a single probe as well as the necessity to go through a learning curve for employing it properly [13]. Moreover, in a previous study, Mitchell-Heggs et al [14] reported the use of ICE probe via transesophageal route without sedation which yielded good results with a high tolerance. However, the feasibility of this approach is not given when the risk of traumatic lesions after the introduction of a small tipped catheter into the esophagus is considered, especially in case of lacking experience.…”
Section: Discussionmentioning
confidence: 99%
“…Although general anesthesia is not necessary for this technique, additional femoral vein puncture is an important limitation like the cost of a single probe as well as the necessity to go through a learning curve for employing it properly [13]. Moreover, in a previous study, Mitchell-Heggs et al [14] reported the use of ICE probe via transesophageal route without sedation which yielded good results with a high tolerance. However, the feasibility of this approach is not given when the risk of traumatic lesions after the introduction of a small tipped catheter into the esophagus is considered, especially in case of lacking experience.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, real-time three-dimensional and minimally invasive transesophageal echocardiography-guided TP have been applied for atrial fibrillation ablation. [16][17][18] Beside repeated TP, left ventricular lead placement may require a side-selective TP. [19][20][21] In some selected procedures a transaortic approach may be an alternative to TP.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, catheters at the aorta, coronary sinus (CS) and His bundle are commonly used. Regarding the procedural time, 1 to 15 minutes have been reported [6][7][8][9][10].…”
Section: -Traditional Transseptal Puncture Proceduresmentioning
confidence: 99%
“…In order to overcome the limitations of the procedures only guided by fluoroscopy, several authors exploited the application of new imaging modalities in TSP (Table 5), namely: transesophageal echocardiography (TEE) [19,[33][34][35][36][37][38], intracardiac echocardiography (ICE) [9,[39][40][41][42][43], real-time magnetic resonance (MR) [44] and direct color visualization [45]. Furthermore, needle tracking based on electromagnetic sensors [46] and electroanatomic mapping (EAM) [17,[47][48][49][50][51][52] were also presented.…”
Section: Intra-procedural Guidance Techniquesmentioning
confidence: 99%